2015
DOI: 10.1055/s-0034-1395589
|View full text |Cite
|
Sign up to set email alerts
|

Eccentric Exercise Leads to Glial Activation but not Apoptosis in Mice Spinal Cords

Abstract: The aim of this investigation was to evaluate the effects of 3 overtraining (OT) protocols on the glial activation and apoptosis in the spinal cords of mice. Rodents were divided into control (C; sedentary mice), overtrained by downhill running (OTR/down), overtrained by uphill running (OTR/up) and overtrained by running without inclination (OTR). The incremental load test, ambulation test, exhaustive test and functional behavioural assessment were used as performance evaluation parameters. 36 h after the exha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
52
1
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(65 citation statements)
references
References 42 publications
8
52
1
4
Order By: Relevance
“…However, here, we verified that the OTR/up group presented a lower change in the exhaustion velocity as compared with the other OT protocols. In addition, differently from Rocha's investigation (da Rocha et al 2015b), we showed that the OTR protocol also reduced the rotarod performance as compared with the CT group. These findings indicate that the application of the same OT protocols in different batches of C57BL/6 mice may induce minimal differences of adaptation.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, here, we verified that the OTR/up group presented a lower change in the exhaustion velocity as compared with the other OT protocols. In addition, differently from Rocha's investigation (da Rocha et al 2015b), we showed that the OTR protocol also reduced the rotarod performance as compared with the CT group. These findings indicate that the application of the same OT protocols in different batches of C57BL/6 mice may induce minimal differences of adaptation.…”
Section: Discussioncontrasting
confidence: 99%
“…Indeed, da Rocha and coworkers (2015b) showed that OTR/down and OTR/up models upregulated the phosphorylation and inhibition of glycogen synthase kinase 3 beta (GSK3β), increasing hepatic glycogen deposition. In accordance with other studies (Zisman et al 2000, Kotani et al 2004, the authors concluded that liver acted as a compensatory organ when skeletal muscle presents insulin signaling impairment (da Rocha et al 2015b).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Although the other two OT protocols performed in uphill and without inclination led to similar decrements in the analyzed performance parameters 3,12,13 , they induced particular modulations of the hepatic insulin signaling pathway 3 . Thus, we also evaluated their effects on the hepatic protein levels of APPL1 and APPL2.…”
Section: Introductionmentioning
confidence: 82%
“…The eight-week OT protocols based on downhill running, uphill running and running without inclination were performed as previously described 13 , and each experimental week consisted of five days of training followed by two days of recovery. During the first four weeks of the OT protocols (i.e.…”
Section: Overtraining Protocols and Performance Evaluationsmentioning
confidence: 99%